Exploring social class dynamics in the novel "Laskar Pelangi": An in-depth analysis - Majid Wajdi; Subekhi Hadi Purnomo; Siti Mariam; Suriyadi Suriyadi; Amrullah Amrullah (Journal of Education, Social & Communication Studies, 2024)
This study goes into the intricate web of social class dynamics depicted in the Indonesian novel "Laskar Pelangi" by Andrea Hirata. Set against the backdrop of Belitung, the narrative unfolds the lives of a group of students as they navigate the challenges of education and dreams. The primary aim of this research is to dissect the nuanced portrayal of social classes within the novel, examining how they shape characters' identities, opportunities, and interactions. To achieve a comprehensive understanding, a qualitative approach is employed, involving close textual analysis of key passages and character interactions. The analysis focuses on identifying and categorizing the various social classes represented in the novel, exploring the factors that contribute to their formation, and elucidating the implications of these class distinctions on character development and societal structures. Themes such as education, economic disparities, and cultural influences are scrutinized to unravel the intricate threads that weave the social tapestry of "Laskar Pelangi." This study concludes by synthesizing the findings, offering a nuanced understanding of how social class dynamics are intricately interwoven into the narrative fabric of "Laskar Pelangi." The novel serves as a microcosm reflecting broader societal structures in Indonesia, shedding light on the complexities and challenges faced by individuals from different social strata. This exploration contributes to the broader discourse on literature and social class, emphasizing the relevance of such analyses in understanding the cultural and societal nuances depicted in literary works.